Enhancing Conceptual Mastery in Elementary Science Through RADEC-Ethnoscience Integration: A Pre-Experimental Study - Yuan Oemar Surindani; Wahyu Sopandi; Cepi Riyana (Papanda Publisher, 2026)
Elementary students frequently struggle with abstract scientific concepts due to traditional pedagogical approaches lacking contextual relevance and cultural meaningfulness. This pre-experimental study employed a one-group pretest-posttest design involving 30 fifth-grade students at SDN 162 Warung Jambu who studied ecosystem harmony through the RADEC (Read, Answer, Discuss, Explain, Create) learning model integrated with an ethnoscience approach. Data were collected using a validated conceptual mastery instrument measuring Bloom's six cognitive levels, analyzed through descriptive statistics, normalized gain calculations, and paired-sample t-tests. The intervention produced significant improvements, with average scores increasing from 58.67% (moderate category) to 84.33% (very high category), yielding an N-Gain of 0.62 (moderate category) and highly significant statistical results (t = 21.89, p < 0.001). Students achieving the Minimum Completion Criteria increased from 26.67% to 93.33%. The most substantial gains emerged at higher-order thinking levels: analyzing (31.00% improvement) and evaluating (28.00% improvement), demonstrating the model's effectiveness in developing sophisticated scientific reasoning. The integration of RADEC and ethnoscience systematically develops conceptual mastery by connecting scientific principles with local cultural knowledge and traditional practices, facilitating deep, contextual understanding. This culturally responsive approach simultaneously achieves cognitive rigor and educational equity, challenging conventional assumptions about elementary students' cognitive capacities while honoring indigenous knowledge systems within formal science education.